Minimalism and fashion : reduction in the postmodern era - Dimant, Elyssa; Costa, Francisco (New York : Collins Design, Imprint of HarperCollins Publishers, 2010)
Minimalism and Fashion examines the minimalist movement in fashion while addressing its confluence with and divergence from similar currents in art, architecture, and design. Organized by decade, the text explores the evolving relationships and influences between fine art and the art of sartorial minimalism, and is accompanied by more than 150 images.
boek